Avian influenza overview August – November 2018. (20th December 2018) - ,; ,; ,; Adlhoch, Cornelia; Brouwer, Adam; Kuiken, Thijs; Miteva, Aleksandra; Mulatti, Paolo; Smietanka, Krzysztof; Staubach, Christoph; Gogin, Andrey; Muñoz Guajardo, Irene; et al.
Abstract : Between 16 August and 15 November 2018, 14 highly pathogenic avian influenza (HPAI) A(H5N8) outbreaks in poultry establishments in Bulgaria and seven HPAI A(H5N6) outbreaks, one in captive birds in Germany and six in wild birds in Denmark and the Netherlands were reported in the European Union (EU). No human infection due to HPAI A(H5N8) and A(H5N6) viruses have been reported in Europe so far. Seroconversion of people exposed during outbreaks in Russia has been reported in one study. Although the risk of zoonotic transmission to the general public in Europe is considered to be very low, appropriate personal protection measures of people exposed will reduce any potential risk. Genetic clustering of the viruses isolated from poultry in Bulgaria suggests three separate introductions in 2016 and a continuing circulation and transmission of these viruses within domestic ducks. Recent data from Bulgaria provides further indication that the sensitivity of passive surveillance of HPAI A(H5N8) in domestic ducks may be significantly compromised. Increased vigilance is needed especially during the periods of cold spells in winter when aggregations of wild birds and their movements towards areas with more favourable weather conditions may be encouraged. Two HPAI outbreaks in poultry were reported during this period from western Russia. Low numbers of HPAI outbreaks were observed in Africa and Asia, no HPAI cases were detected in wild birds in the time period relevant for this report. Although a few HPAI outbreaks were reported in Africa and Asia during the reporting period, the probability of HPAI virus introductions from non‐EU countries via wild birds particularly via the north‐eastern route from Russia is increasing, as the fall migration of wild birds from breeding and moulting sites to the wintering sites continues. Furthermore, the lower temperatures and ultraviolet radiation in winter can facilitate the environmental survival of any potential AI viruses introduced to Europe.